Hubungan Hipoalbuminemia dengan Mortalitas Pasien Pneumonia di RSUD Subang Tahun 2020-2022 - Siti Fani Farida Hendrik; Ieva Baniasih Akbar; Widayanti (UNISBA Press, 2024)
Abstract. Pneumonia is an infectious disease that is a health problem in both developing and developed countries with a high mortality rate. Based on Riskesdas 2018, the incidence of pneumonia in Indonesia has increased by 1% from 2013. In addition, pneumonia is included in the ten diseases with the highest of case fatality rate (CFR) highest in Indonesia. Pneumonia is an inflammatory condition with high catabolism which can cause a decrease in albumin levels in the blood. This situation makes examining serum albumin levels an objective examination in determining the severity of pneumonia patients. This study aims to analyze the relationship between the degree of hypoalbuminemia and mortality status in pneumonia patients at Subang District Hospital in 2020-2022. This research is a analytic correlation study using a cross-sectional study. Data collection used secondary data from medical records of 70 patients who experienced pneumonia at Subang District Hospital in 2020-2022. Data were analyzed using univariate and bivariate tests and analyzed using tests Chi-Square. The majority of pneumonia patients in this study were >65 years old and male. The majority of patients experienced moderate hypoalbuminemia, 52 patients (74%) with a mortality rate in pneumonia patients of 49% or 30 patients. The Chi-Square test shows a p value of 0.012 where the P value is smaller than 0.05. There is a relationship between albumin levels and the mortality status of pneumonia patients at Subang District Hospital, West Java in 2020-2022. Abstrak. Pneumonia merupakan salah satu penyakit menular yang menjadi masalah kesehatan baik di negara berkembang maupun di negara maju dengan angka kematian yang tinggi. Berdasarkan Riskesdas 2018 angka kejadian pneumonia di Indonesia mengalami kenaikan sebesar 1% dari tahun 2013. Selain itu pneumonia termasuk kedalam sepuluh penyakit dengan angka case fatality rate (CFR) tertinggi di Indonesia. Pneumonia merupakan kondisi inflamasi dengan katabolisme yang tinggi sehingga dapat menyebabkan penurunan kadar albumin didalam darah. Keadaan tersebut menjadikan pemeriksaan kadar albumin serum menjadi pemeriksaan objektif dalam menentukan keparahan pasien pneumonia. Penelitian ini bertujuan untuk menganalisis hubungan antara derajat hipoalbuminemia dengan status mortalitas pada pasien pneumonia di RSUD Subang tahun 2020-2022. Penelitian ini merupakan penelitian analitik korelasi menggunakan studi potong lintang. Pengumpulan data menggunakan data sekunder dari rekam medis 70 pasien yang mengalami pneumonia di RSUD Subang tahun 2020-2022. Data di analisis menggunakan uji univariat dan bivariat dan dianalisis menggunakan uji Chi-Square. Mayoritas pasien pneumonia pada penelitian ini berusia >65 tahun dan berjenis kelamin laki-laki. Mayoritas pasien mengalami hipoalbuminemia sedang sebanyak 52 pasien (74%) dengan angka kematian pada pasien pneumonia sebesar 49% atau sebanyak 30 pasien. Uji Chi-Square menunjukan nilai p sebesar 0.012 dimana nilai P lebih kecil dari 0.05. Terdapat hubungan antara kadar albumin dengan status mortalitas pasien pneumonia RSUD Subang Jawa Barat tahun 2020-2022. Kadar albumin menurun dapat menjad tanda keparahan pasien pneumonia.